Genotype × Environment Interaction and Correlations Between Agronomic Traits, Flowering, and Fruit Set in Cassava - Luana da Silva Guedes; Massaine Bandeira e Sousa; Eder Jorge de Oliveira (Horticulturae, 2025)
The lack of synchronization and low flowering rates in cassava (Manihot esculenta Crantz) present significant challenges for breeding programs. This study evaluated (i) genetic variability in flowering and fruiting; (ii) genotype × environment interactions and climatic influences on flowering; and (iii) correlations between plant architecture, flowering traits, and yield. Two field experiments were conducted with 290 and 343 genotypes, respectively. From 4 months after planting (MAPs), flowering and fruiting traits were monitored monthly. At 12 MAPs, plant architecture, root yield, and quality traits were assessed. Genotypes were grouped using discriminant analysis of principal components (DAPC). The results showed significant genetic variability for flowering and fruiting. About 76% of genotypes flowered in both environments, while 24% flowered in only one. Early flowering (by 4 MAPs) occurred in 86% of genotypes. Five distinct genotype groups were identified, with Group 1 showing superior flowering and early onset. Optimal flower production occurred at mean daily temperatures within the range 21.5–24 °C in Experiment 2. However, no significant correlations were found between flowering and yield traits. This study provides insights into cassava flowering dynamics and supports breeding efforts to develop improved populations with more-predictable flowering behavior.